Imaging of microglia in patients with neurodegenerative disorders - Politis, Marios; Su, Paul; Piccini, Paola (Frontiers in Pharmacology, 2012)
Microglia constitute the main immune defense in the central nervous system. In response to neuronal injury, microglia become activated, acquire phagocytic properties and release a wide range of pro-inflammatory mediators that are essential for the annihilation of the neuronal insult. Although the role of microglial activation in acute neuronal damage is well defined, the pathophysiological processes underlying destructive or protective role to neurons following chronic exposure to microglial activation is still a subject of debate. It is likely that chronic exposure induces detrimental effects by promoting neuronal death through the release of neurotoxic factors. Positron emission tomography imaging with the use of translocator protein (TSPO) radioligands provides an in vivo tool for tracking the progression and severity of neuroinflammation in neurodegenerative disease. TSPO expression is correlated to the extent of microglial activation and the measurement of TSPO uptake in vivo with PET is a useful indicator of active disease. Although understanding of the interaction between radioligands and TSPO is not completely clear, there is a wide interest in application of TSPO imaging in neurodegenerative disease. In this article, we aim to review the applications of in vivo microglia imaging in neurodegenerative disorders such as Parkinson’s disease, Huntington’s disease, Dementias and Multiple Sclerosis.